A case study on floods at Rantau Panjang, Kelantan - Rosnadia, Rosli (2012)
The title of this study is A Case Study on Floods of 2010 and 2011 in Kelantan, Malaysia. This study focuses on causes and impacts of the floods occurred to the people, government and also nation. There are two main objectives of this study, which are firstly is to analyzed the floods occurred on November 2010 till January 2011 and secondly is to study the flood hazard management in Malaysia. To complete this study, a few of the interviewed with the Engineer from Drainage and Irrigation Department of Malaysia need to be done. The obtained data will be analyzed to find the main cause of the floods occurred. By comparing with previous study, the flood hazard management in Malaysia will be advanced in order to control the floods occurred and for the better life in future.